3D pore system reconstruction using nano-scale 2D SEM images and pore size distribution analysis for intermediate rank coal matrix; Fuel; Vol. 275 - Roslin A. A. Aleksandra Aleksandrovna; Pokrajac D. Dubravka; Wu Kejian; Zhou Yingfang (2020, 2020)
Title screen